2013
DOI: 10.1111/jne.12084
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin Neurones do not Directly Signal to RFRP‐3 Neurones but RFRP‐3 may Directly Modulate a Subset of Hypothalamic Kisspeptin Cells in Mice

Abstract: The neuropeptides kisspeptin (encoded by Kiss1) and RFamide-related peptide-3 (also known as GnIH; encoded by Rfrp) are potent stimulators and inhibitors, respectively, of reproduction. Whether kisspeptin or RFRP-3 might act directly on each other’s neuronal populations to indirectly modulate reproductive status is unknown. To examine possible interconnectivity of the kisspeptin and RFRP-3 systems, we performed double label in-situ hybridization (ISH) for RFRP-3’s receptors, Gpr147 and Gpr74, in hypothalamic K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 51 publications
6
88
1
1
Order By: Relevance
“…In tandem with an unprecedented level of RFRP-3 control over pubertal activation, we also document the presence of RFRP-3-producing neurons in the Arc, a chief site of kisspeptin synthesis in other mammalian species (65). In contrast to the small proportion of Kiss1/GPR147 coexpressing cells in other areas of the rodent brain, 25% of kisspeptin somata in the mouse Arc express GPR147 or GPR74, whereas 35% receive contact from RFRP fibers (66). Further, RFRP KO mice show higher numbers of Kiss1 positive neurons and increased total Kiss1 gene expression, specifically in the Arc (35).…”
Section: Discussionmentioning
confidence: 82%
“…In tandem with an unprecedented level of RFRP-3 control over pubertal activation, we also document the presence of RFRP-3-producing neurons in the Arc, a chief site of kisspeptin synthesis in other mammalian species (65). In contrast to the small proportion of Kiss1/GPR147 coexpressing cells in other areas of the rodent brain, 25% of kisspeptin somata in the mouse Arc express GPR147 or GPR74, whereas 35% receive contact from RFRP fibers (66). Further, RFRP KO mice show higher numbers of Kiss1 positive neurons and increased total Kiss1 gene expression, specifically in the Arc (35).…”
Section: Discussionmentioning
confidence: 82%
“…Strikingly, we found that both the number of Rfrp neurons and total Rfrp mRNA dropped significantly, by 30% and 40%, respectively, between PND 15 and PND 21, after which they stabilized at adult levels. This large decrease in Rfrp expression over the course of a few days may point to this particular peripubertal stage as a critical period for a reduction of RFRP-3-mediated inhibition of GnRH or kisspeptin neurons (Poling et al, 2013). Notably, this drop in Rfrp expression occurs almost a week prior to VO, suggesting that hypothalamic changes in reproductive circuits occur well before external physical signs of pubertal onset.…”
Section: Discussionmentioning
confidence: 99%
“…Double-label ISH was performed as previously described (35,36). Briefly, one set of slide-mounted brain sections encompassing the entire DMN were fixed in 4% paraformaldehyde, pretreated with acetic anhydride, rinsed in 2× SSC (sodium citrate, sodium chloride), delipidated in chloroform, dehydrated in ethanols, and air-dried.…”
Section: Methodsmentioning
confidence: 99%